A Linguistic Study of Derivational and Inflectional Morphology in Folklore’s Lyric Composition - Ko, Seung Youl; Lodong, Agnechia Friska Rivalny (IKIP Siliwangi, 2025)
This study aims to explore derivational and inflectional word-formation processes, including regular and irregular forms in the song lyrics of Taylor Swift’s Folklore album. It addresses two research questions: (1) What are the types of derivational and inflectional morphemes found in the lyrics? and (2) How do these morphemes contribute to the overall word formation in the lyrics? A total of 16 songs were selected from Taylor Swift’s official YouTube Music channel to ensure authenticity and credibility. Employing a descriptive-qualitative research method, each song was analyzed word by word to identify words of derivational or inflectional word formation. The selected words were organized by song and categorized accordingly into each table on Google Sheets. Duplicated entries were eliminated to retain only one representative word for each song. The total number of words and each word formation were exhibited in Table 1, and each representative word from each subtype was arranged in Table 2, followed by a detailed morphological analysis in the discussion. Findings reveal regular inflectional morphemes such as -ed, -s, -est, etc., and irregular forms like was, were, didn’t, etc. Derivational morphemes included -ness, -ly, -tion, etc. Furthermore, several words exhibited combined word formations, such as convictions.